2008
DOI: 10.1016/j.abb.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of rapid lipogenesis in insulin secretion: Insulin secretagogues acutely alter lipid composition of INS-1 832/13 cells

Abstract: Pancreatic beta cell mitochondria convert insulin secretagogues into products that support insulin exocytosis. We explored the idea that lipids are some of these products formed from acyl group transfer out of mitochondria to the cytosol, the site of lipid synthesis. There are two isoforms of acetyl-CoA carboxylase, the enzyme that forms malonyl-CoA from which C 2 units for lipid synthesis are formed. We found that ACC1, the isoform seen in lipogenic tissues, is the only isoform present in human and rat pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 54 publications
(96 reference statements)
10
71
0
Order By: Relevance
“…This would facilitate the docking interaction between the ISG membrane and the plasma membrane, as mentioned above. Taken together, the current data combined with recent data that showed that PS is concentrated in ISG (1) further suggest that PS and its increase in beta cells (55) with glucose stimulation (1) is important for insulin secretion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This would facilitate the docking interaction between the ISG membrane and the plasma membrane, as mentioned above. Taken together, the current data combined with recent data that showed that PS is concentrated in ISG (1) further suggest that PS and its increase in beta cells (55) with glucose stimulation (1) is important for insulin secretion.…”
Section: Discussionsupporting
confidence: 52%
“…The presence of ATP9A in the trans-Golgi network implicates this P4 ATPase in vesicle biogenesis. The PS data (1,55) combined with the current flippase data suggest that the inhibition of stimulated-insulin release is due to inhibition of translocation of PS to the cytosolic leaflets of the ISG and plasma membrane lipid bilayers, where the negatively charged PS acts as a coupling factor enhancing the zipperinglike fusion of the positively charged amino acid domains of secretory vesicle SNARE proteins and the positively charged amino acid domains of the plasma membrane SNARE proteins (2-7). The inhibition of this translocation should inhibit the docking and fusion of the ISG with the plasma membrane during insulin exocytosis and would inhibit glucose-stimulated insulin release.…”
Section: Resultsmentioning
confidence: 99%
“…This was demonstrated by the knockdown experiment in which suppression of this enzyme expression impairs GSIS in -cells (MacDonald et al, 2005). Acute exposure of -cells to glucose not only stimulates rapid lipogenesis but also alters phospholipid and cholesteryl ester contents in the plasma membrane which in turn affects insulin granule exocytosis and -cell plasma membrane fluidity (MacDonald et al, 2008). Fig.…”
Section: K Atp -Independent Gsis: Anaplerosis and Coupling Factorsmentioning
confidence: 95%
“…De novo fatty acid synthesis would seem to be the only outlet for the products (NADPH and malonyl-CoA) of a pyruvate/citrate cycle. However, fatty acid synthase is poorly expressed in rat islets (72), while data from INS-1 832/13 cells suggested that only ϳ2% of the total glucose utilized in high glucose was incorporated into lipid (248), although Macdonald and coworkers (313,317) presented qualitative evidence that islets and INS-1 cells perform significant fatty acid synthesis. Note that even if a pyruvate/citrate cycle were to generate stoichiometric lipids, this would not in itself clarify a mechanism for the cycle to facilitate GSIS.…”
Section: Pyruvate/citrate Cyclementioning
confidence: 99%